Planning for rural development administration - Sharma, Aruna; Rajagopal (New Delhi, 1995)
Rural development is a comprehensive subject but in no sense is complex. The rural development administration, webbed in a multi-agency system, often makes the development issues more intricate. Consequently, an administrator spends a long time of his incumbency period in figuring out the procedural path to bridge the nexus between imple mentation of programmes and their end benefits. Are we following a right path of rural development with a blend of theoretical, applied and management concepts? The book attempts to reach a prolific dialogue of this long debated issue. The discussions presented in this book unveil the other side of the rural development administration as required for making structural adjustments in ensuring every effort a milestone.
Keywords: Rural development